Antología poética mercedaria - Tajuelo Gallego, León (O. de M.); María Pemán, José pr; Ciudad Rodrigo, Juan de (O. de M.); Medina, Pedro de (O. de M.); Serna, Pedro de la (O. de M.), fray; Ballester, Francisco (O. de M.); Rojas Ausa, Juan de (O. de M.); Lisbona Pueyo, Ramón (O. de M.); Sancho Aguilar, Manuel (O. de M.); Alonso Vega, Eugenio (O. de M.); Sancho Blanco, Amerio (O. de M.); Salgueiro Vázquez, Egidio (O. de M.); et al. ([s.n.], 1954)
Contiene las obras poéticas de los siguientes mercedarios/as: Juan de Ciudad Rodrigo, Miguel de Alonsotegui, Pedro de Medina, Alonso Remón, Pedro de J.Mº de la Serna, Tirso de Molina, Fancisco Ballester, Juan de Rojas Ausa, Juan Interian de Ayala, Ramón Lisbona Pueyo, Manuel Sancho Aguilar, Eugenio Alonso Vega, Amerio Sancho Blanco, Egidio Salgueiro Vázquez, Miguel Escanez Mingorance, Jose Cereijo Muiños, Liborio Mir Antolín, Gumersindo Placer López, José S. Crespo Pozo, León Tajuelo Gallego, Antonio Vázquez Fernández, Juan Devesa, Gumersindo Devesa, Agnelio Hurtado, Reginaldo Delgado, Pedro Armengol Ferreyra, José León Pérez, Luis G. Marquez Eyzaguirre, Juan B. Herrada, María de la Antigua, Mª de la Asunción Tajuelo Gallego, Margarita Mª López Maturana, Mª de los Ángeles G. Mata, Mª Begoña Docha, Mª de la Asunción López, Mª Fernanda E. Infantes, M. Carmen R. Santos, Mª de las Mercedes Biain, M. Jesús del Dulce N. Torres Cañamares, Mª de los Ángeles de Ribot y Mª Lucía Román